Functional outcome of proximal humerus fractures treated with open reduction and internal fixation using proximal humerus locking plate: a prospective hospital-based study - Sardar, Rudra; Roy, Rajiv; Ahmed, Arshad; Poria, Rajkumar; Mallick, Dibakar (International Journal of Research in Orthopaedics, 2026)
Background: Proximal humerus fractures account for 4-6% of all fractures and may result in significant functional impairment when displaced and inadequately treated.1 Locking plate fixation offers angular stability and improved fixation, particularly in osteoporotic bone.2,3 Methods: This prospective hospital-based study was conducted from June 2023 to July 2024. Thirty patients aged 18–65 years with acute displaced Neer two-part and three-part proximal humerus fractures were treated with open reduction and internal fixation using proximal humerus locking plates through a deltopectoral approach. Functional outcome was assessed using the Constant-Murley score and DASH score. Radiological union and complications were documented. Statistical analysis was performed using chi-square tests. Results: The mean age was 44 years, with female predominance (60%). Two-part fractures constituted 60% and three-part fractures 40%. Radiological union was achieved in all cases. Functional outcomes were excellent in 20%, good in 50%, moderate in 20%, and poor in 10% of patients. Early surgery (≤5 days) and two-part fractures were significantly associated with better outcomes (p<0.05). Late complications such as stiffness and malunion negatively influenced outcomes (p=0.002). Conclusions: Open reduction and internal fixation using proximal humerus locking plates provides reliable union and satisfactory functional outcomes in displaced proximal humerus fractures when performed early and with appropriate patient selection.